A Study on Conversion of Higher Sulfur Pig Iron to Ductile Iron Using In-Mold Treatment Technique - Mohd Rashidi, Maarof; Mohd Hasbullah, Idris (Praise Worthy Prize S.r.l, 2012)
Processing of iron will never stop. The demand of selected iron properties is depend on market requirement. Conventional ductile iron is one of the main components for industrial used. It is developed to have different microstructure compare to ordinary iron. It has nodule graphite compare to flake graphite. The conversion is succeeded using magnesium treatment. But, the processing of ductile iron required low sulfur content in iron composition due to magnesium treatment respond. Sulfur reacts with magnesium during melting. Thus, the conversion of flake to nodule shape is disturbed. To minimize the reaction, magnesium treatment using an In-Mold treatment is utilize. In-Mold technique is known as late magnesium treatment. It minimizes magnesium from fade away during melting. Therefore this study is performed purposely to investigate the conversion of higher sulfur iron using In-Mold technique. A group of heats were melted and test conducted to explore its microstructure and mechanical properties. It was discovered that the graphite shape was nodule. Hardness and tensile strength was related with percentage of magnesium treatment used.